Elective repair of uncomplicated inguinal hernia in south eastern nigerian - Ugwu-Olisa, Ogbuanya Aloysius; Ogadi, Emedike Samuel Chukwuemeka (Asian Journal of Medical Sciences, 2015)
Aims and Objectives: Inguinal hernia repair is the most common operation in general surgery worldwide. Elective repair to safeguard complications is recommended because outcomes of early repair are uniformly superior to results of emergency operations. This study aimed to document our own experiences with regards to elective repair of uncomplicated inguinal hernia and compare our findings with previous data. Materials and Methods: This is a descriptive prospective study of 261 consecutive patients with uncomplicated inguinal hernias repaired electively at Federal Teaching Hospital, Abakaliki, southeastern Nigeria between January 2010 to December 2012. Relevant data extracted and analyzed with SPSS version 22.0 included patients’ demographics, clinical details, surgical repairs and outcome measures. Result: A total of two hundred and sixty one patients with 306 uncomplicated inguinal hernias repaired electively were enrolled. The age range of the patients was 2 months – 88 years with a mean age of 35.7 ± SD 16.6. Majority (46.4%) of the patients presented with hernias on the right side, the rest either had hernias on the left(36.4%) or both sides (17.2%). At operation, 203 (66.3%) hernias were indirect, 96 (31.4%) direct and 7 (2.3%) pantaloon hernias. Modified Bassini repair was used in the majority (66.7%) of patients. Complications occurred in only 9.7% of repairs. At a median follow up of 8 months, 1 (0.3%) hernia recurrence was seen. No mortality was recorded. Conclusion: Inguinal hernias in our environment are very common, but often neglected. Our results show that elective repair is critical for preventing devastating complications and ensuring successful surgical outcomes. Asian Journal of Medical Sciences Vol.7(2) 2015 90-95